The Effect Of Brain Gym For Kognitif Function In Elderly Kendari City Healtyh Center: Brain Gym For Kognitif Function - Armayani, Armayani; Said, Faridah Mohd; Nambiar , Nisha; Nurlila, Ratna Umi (STIKes Mandala Waluya Kendari, 2024)
Background: World Health Organization Stated that dementia is experienced by the elderly aged 60-74 years by 15-20%, 75-85 years by 5-15%. The older the age, the greater the prevalence and the heavier the type of dementia experienced by the elderly. This study aims to determine the effect of brain exercise on the cognitive function of the elderly at the Public Health Center of Kendari City. Methods: : The design of this research is quasi experiment with pre and post test without control with quota sampling technique. The population in this study amounted to 125 people and the sample in this study was the elderly who experienced cognitive function disorders at the Perumnas Public Health Center as many as 15 people. Data analysis used the statistical paired sample t-test. The data collection tool used is the Mini Mental Status Examination questionnaire. Results: The results of this study indicate t count (12,646) > t table (6.714) and p value 0.000 <0.05 so Ho is rejected, meaning that there is an effect of brain exercise on the cognitive function of the elderly. Conclusions: It is hoped that the Public Health Center will pay more attention to the condition of the elderly who are in the working area of the Perumnas Health Center in order to minimize the risk of cognitive function disorders and carry out brain exercises for the elderly when the Posyandu for the elderly is carried out.